Anti-Inflammatory and Chemopreventive Effects of Bryophyllum pinnatum (Lamarck) Leaf Extract in Experimental Colitis Models in Rodents - Andrade, Anderson Wilbur Lopes; Guerra, Gerlane Coelho Bernardo; de Souza Araújo, Daline Fernandes; de Araújo Júnior, Raimundo Fernandes; de Araújo, Aurigena Antunes; de Carvalho, Thaís Gomes; Fernandes, Júlia Morais; Diez-Echave, Patrícia; Hidalgo-García, Laura; Rodriguez-Cabezas, Maria Elena; Gálvez, Julio; Zucolotto, Silvana Maria (Frontiers in Pharmacology, 2020)
Inflammatory bowel diseases, mainly ulcerative colitis and Crohn’s disease are characterized by chronic inflammation in the intestine. Currently several therapeutic strategies available to treat inflammatory bowel diseases. Though, most treatments can be associated with serious adverse effects what justifies the search for new treatments. In this sense, we highlight the interest in herbal products rich in bioactive compounds which immunomodulatory and antioxidant properties as is the case of Bryophyllum pinnatum (Crassulaceae). This plant is used in traditional medicine in Brazil for treating inflammatory diseases. We hypothesized that hydroethanolic B. pinnatum leaf extract has intestinal anti-inflammatory effects on two experimental colitis models: 2.4-dinitrobenzene sulfonic acid (DNBS) in rats, and dextran sulfate sodium (DSS) in mice. Ultra-fast liquid chromatography method used for the quantification of the main compounds indicated good linearity, specificity, selectivity, precision, robustness and accuracy. The major flavonoids (mg/g of the extract) quantified were: quercetin 3-O-α-L-arabinopyranosyl-(1-2)-α-L-rhamnopyranoside (35.56±0.086 mg/g), kaempferol 3-O-α-L-arabinopyranosyl-(1-2)-α-L-rhamnopyranoside (4.66±0.076 mg/g) and quercetin-3-O-rhamnopyranoside (4.56±0.026 mg/g). The results obtained in the DNBS and DSS models indicate that extract has both chemopreventive and anti-inflammatory effects, observing a significant reduction in the disease activity index score, and less macroscopic and microscopic damage. The extract promoted downregulation of Toll-like receptor and kappa B p65 nuclear factor gene expression, leading to a reduction in pro-inflammatory and oxidative mediators, chemokines, and cell adhesion molecules. This immunomodulatory property was proposed that one of the possible action mechanisms of extract. An improvement in intestinal damage was also associated with a reduction in oxidative stress and infiltration of leukocytes, as evidenced by the reduction in malonaldialdehyde and myeloperoxidase activity and increase in total glutathione in the colonic tissue. Moreover, the extract improved the cytoarchitecture of the colonic tissue and the integrity of the intestinal epithelial barrier by restoring the expression of the proteins associated with mucosa protection. In view of the beneficial effects showed by the B. pinnatum leaf extract in preclinical rodent models of colitis there is the potential to conduct some future clinical studies to ensure safe and effective development of a phytotherapeutic treatment for human inflammatory bowel diseases.